Acute Toxicity Test with Daphnia magna: An Alternative to Mammals in the Prescreening of Chemical Toxicity? - Guilhermino, Lúcia (2000)
In this study, the association between the acute toxicity of 15 compounds to Daphnia magna, expressed as 24- and 48-h LC50 values, and the corresponding oral LD50 values for the rat was tested. Since there was evidence of a strong relationship between the two species, the sample was extended to 54 cases by including the values for acute toxicity to D. magna and rat of more chemicals published by other authors. Thus, a total of 54 data points were further used to ascertain the relationship between the acute toxicity of chemical compounds to D. magna and that to the rat. To summarize its validity, the D. magna test is more specific than sensitive as an indicator of toxicity to the rat. When it is used with a chemical that has a high probability of being very toxic to D. magna (LC50< 0.22 mg/L), the test provides considerable information if it is positive, virtually giving evidence of toxicity to the rat (with a probability of 0.83). On the other hand, a negative test (D. magna LC50>0.22 mg/L) has a probability of correctly assigning nontoxicity to the rat equal to 0.74. This study and results published by other authors provide good evidence of the applicability of using invertebrate tests as prescreening methods, thus considerably reducing the number of mammals required in toxicity testing.